(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2015)
This paper is to investigate the use of solar energy in desalination by humidification and dehumid- ification process (HD). Here, a proposal for the desalination unit has been come out with cylindrical shape containing the evaporator in the middle and surrounded by the condenser. The hot feed water coming from the solar thermal system is sprayed at the top of the evaporator where the air flows from the bottom. In the evaporator the air is humidified until it gets out saturated, then introduced to the condenser, where it is dehumidified to obtain the fresh water and circulated back to the evaporator. Practically there are many parameters influence on the performance of this desalination unit, which are environmental, design and operational. In the current study these parameters are taken in consideration to formulate mathematical models which govern the performance of the main components of this unit, which are the evaporator, the condenser and the solar thermal system. The deduced mathematical models have been interpreted in many programs in visual basic language as a computer software. This software contains many pages which help in introducing and analyzing the most influential parameters. In this case many operational parameters have been studied such as feed water temperature, mass flow rate and salinity, in addition to cooling water mass flow rate and inlet temperature, as well as quantity of solar irradiance with others. At these inputs many outputs have been obtained which are related to the performance of the desalination unit such as fresh water productivity, energy consumption, humidifier volume, recovery ratio and gain output ratio.